Contextual Meaning in Literary Translation: A Semantic–Pragmatic Analysis (The Peerian Journal, 2026)
This article examines contextual meaning in literary translation from a semantic-pragmatic perspective. Contextual meaning is understood as a dynamic construct emerging from the interaction between linguistic units and their textual, situational, and cultural environments. The study focuses on the translation of lexical and phraseological units, which are highly sensitive to contextual variation. Using qualitative methods, including semantic, pragmatic, and comparative analysis, the research demonstrates that successful literary translation depends not on literal word substitution but on the reconstruction of meaning through contextual interpretation. The findings highlight that translation is a cognitive and interpretative process requiring both linguistic and cultural competence